(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
Corona Virus Disease (COVID-19), a threat to global public health, caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) has now spread to more than two hundred countries in the world. This ongoing pandemic has already been exhausted our health care systems. So determining or predicting the need of healthcare resources has now become a number one priority and the length of hospitalization is a scale which represents the function of the health system of countries. Our objectives were to see the length of hospital stay of COVID-19 patients and its relationship with liver function abnormalities. This obser- vational cross-sectional study was carried out in the COVID-19 inpatient department of BSMMU on 96 patients who are RT-PCR positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Liver function abnormalities (ALT, AST, ALP, PT, serum biliru- bin and serum albumin) were recorded precisely. Length of hospital stay was documented. Occurrence of liver function abnormalities and their relation with length of hospital stay were assessed statistically. Total 96 patients were included. Mean hospital stay was found to be 14.0±6.2 with range from 5.0 to 33 days. Total 49(51.0%) patients required hospital staying ≤14 days and 47(49%) patients were found hospital stay > 14 days. Mean length of hospital stay in case of mild COVID-19 patients was 6.76±1.12 days, in case of moderate Covid-19 patients was 12.22±1.91 days and in severe group it was 19.18±4.81 days. The mean length of hospital stay was statistically significant with raised ALT (18.9±6.2), raised AST(18.9±5.9) and low serum albumin (19.4±7.1) group (p<0.05). No significant association was found between mean length of hospital stay and raised ALP, PT and S. bilirubin group. This study showed that length of hospital stay were significantly higher among severe COVID-19 patients and among liver function abnormalities raised ALT, raised AST and low serum albumin were associated with significant longer hospital stay. Assessing the length of hospital stay is helpful in under- standing and predicting hospital bed demand and optimizing the use of healthcare resources. BSMMU J 2021; 14 (COVID -19 Supplement): 8-12